2006
DOI: 10.1002/jmv.20775
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human T‐cell lymphotropic virus type 2 (HTLV‐II) from people living in urban areas of Sao Paulo city: Evidence of multiple subtypes circulation

Abstract: Two hundred ninety-three individuals, who were enrolled in the HTLV out-clinic in Sao Paulo city, Brazil, between July 1997 and May 2003, were tested by EIAs, and positive sera 232 (79%) reactive by one of the tests. When these sera were tested by WB revealed 134 were HTLV-I, 28 HTLV-II, 4 HTLV-I/II, and 48 were indeterminate. Polymerase chain reaction (PCR) on the indeterminate group showed that 20 (42%) were HTLV-II and 28 were negative. From a total of 48 HTLV-II subjects with DNA available, restriction fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
2
20
0
2
Order By: Relevance
“…19 Still, the amino acid change S1909P in 100% of the env sequences was also previously reported in Brazilian strains, and could represent a molecular signature of HTLV-2a (variant 2c) strains from Brazil. 21,29 In relation to the tax sequences, the present results corroborated the previous reports that characterize the Brazilian HTLV-2c variant (often considered a molecular variant of -2a), highlighting the long Tax protein. 7,13,15 In addition, high similarity in tax was observed among isolates from the present study (99.9%) and also in relation to the Mo prototype (99.3%).…”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…19 Still, the amino acid change S1909P in 100% of the env sequences was also previously reported in Brazilian strains, and could represent a molecular signature of HTLV-2a (variant 2c) strains from Brazil. 21,29 In relation to the tax sequences, the present results corroborated the previous reports that characterize the Brazilian HTLV-2c variant (often considered a molecular variant of -2a), highlighting the long Tax protein. 7,13,15 In addition, high similarity in tax was observed among isolates from the present study (99.9%) and also in relation to the Mo prototype (99.3%).…”
Section: Figsupporting
confidence: 90%
“…13,15,21 The phylogenetic tree of the env region showed the presence of a group almost exclusively of IDUs, also found in the LTR and tax trees. These clades could represent a different route of virus transmission among IDUs or a little diverse evolutionary virus rate, as described in European IDUs.…”
Section: Figmentioning
confidence: 87%
See 1 more Smart Citation
“…A total of 615 individuals had been seen in the HTLV out-clinic at Emilio Ribas from July 1997 to March 2009. Using our algorithm published previously [Novoa et al, 2007], 104 HTLV-2-infected subjects were disclosed in the last 12 years. For this study, we randomly chose 29 samples that filled the full criteria for HTLV-2 infection and 21 samples from individuals who were indeterminate WB.…”
Section: Methodsmentioning
confidence: 99%
“…Tests that used only lysate of HTLV-1 virus did not show sufficient sensitivity for detecting antibodies against HTLV-2 [Zehender et al, 1997;Waziri et al, 2000]. A recent study in our laboratory found that 50% of samples from a high-risk population identified by WB as indeterminate were HTLV-2 by PCR [Novoa et al, 2007].…”
Section: Introductionmentioning
confidence: 95%